Question
upstudy study bank question image url

The function \( f(x)=\frac{21}{x} \) is one-to-one. a. Find an equation for \( f^{-1}(x) \), the inverse function. b. Verify that your equation is correct by showing that \( f\left(f^{-1}(x)\right)=x \) and \( f^{-1}(f(x))=x \). A. \( f^{-1}(x)=\frac{21}{x} \), for \( x \neq 0 \) B. \( f^{-1}(x)=\square \), for \( x \geq \square \) C. \( f^{-1}(x)=\quad \), for all \( x \) D. \( f^{-1}(x)=\square \), for \( x \leq \square \) b. Verify that the equation is correct. \[ \begin{array}{rlrlrl} \mathrm{f}\left(\mathrm{f}^{-1}(\mathrm{x})\right) & =\mathrm{f}(\square) & \text { and } & \mathrm{f}^{-1}(\mathrm{f}(\mathrm{x})) & =\mathrm{f}^{-1}(\square) & \\ & =\square & & \text { Substitute. } \\ & =\square & & \text { Simplify } . \end{array} \]

Ask by Lynch Mathis. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The inverse function is \( f^{-1}(x) = \frac{21}{x} \) for \( x \neq 0 \). To verify: - \( f(f^{-1}(x)) = x \) - \( f^{-1}(f(x)) = x \) These confirm that the inverse is correct.

Solution

To solve the problem, we will follow the steps outlined: ### Part a: Find the Inverse Function 1. **Start with the function**: \[ f(x) = \frac{21}{x} \] 2. **Replace \( f(x) \) with \( y \)**: \[ y = \frac{21}{x} \] 3. **Swap \( x \) and \( y \)** to find the inverse: \[ x = \frac{21}{y} \] 4. **Solve for \( y \)**: - Multiply both sides by \( y \): \[ xy = 21 \] - Divide both sides by \( x \): \[ y = \frac{21}{x} \] 5. **Thus, the inverse function is**: \[ f^{-1}(x) = \frac{21}{x} \] ### Part b: Verify the Inverse Function We need to verify that: 1. \( f(f^{-1}(x)) = x \) 2. \( f^{-1}(f(x)) = x \) #### Verification of \( f(f^{-1}(x)) \) 1. **Substitute \( f^{-1}(x) \) into \( f(x) \)**: \[ f(f^{-1}(x)) = f\left(\frac{21}{x}\right) \] 2. **Calculate \( f\left(\frac{21}{x}\right) \)**: \[ f\left(\frac{21}{x}\right) = \frac{21}{\frac{21}{x}} = \frac{21 \cdot x}{21} = x \] #### Verification of \( f^{-1}(f(x)) \) 1. **Substitute \( f(x) \) into \( f^{-1}(x) \)**: \[ f^{-1}(f(x)) = f^{-1}\left(\frac{21}{x}\right) \] 2. **Calculate \( f^{-1}\left(\frac{21}{x}\right) \)**: \[ f^{-1}\left(\frac{21}{x}\right) = \frac{21}{\frac{21}{x}} = \frac{21 \cdot x}{21} = x \] ### Conclusion Both verifications confirm that the inverse function is correct. Therefore, the answers are: - **A**: \( f^{-1}(x) = \frac{21}{x} \), for \( x \neq 0 \) - **B**: \( f^{-1}(x) = \frac{21}{x} \), for \( x \geq 0 \) - **C**: \( f^{-1}(x) = \frac{21}{x} \), for all \( x \) - **D**: \( f^{-1}(x) = \frac{21}{x} \), for \( x \leq 0 \) And the verification results are: \[ \begin{array}{rlrlrl} f(f^{-1}(x)) & = f\left(\frac{21}{x}\right) & \text{ and } & f^{-1}(f(x)) & = f^{-1}\left(\frac{21}{x}\right) & \\ & = x & & \text{ Substitute. } \\ & = x & & \text{ Simplify. } \end{array} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the inverse function \( f^{-1}(x) \), we start with \( f(x) = \frac{21}{x} \). To find the inverse, we set \( y = f(x) \) which gives us \( y = \frac{21}{x} \). Now, we solve for \( x \) in terms of \( y \): 1. Multiply both sides by \( x \): \( yx = 21 \) 2. Solve for \( x \): \( x = \frac{21}{y} \) Thus, the inverse function is \( f^{-1}(x) = \frac{21}{x} \). Now we can verify that this equation is correct by showing both compositions return the original values. For \( f(f^{-1}(x)) \): \[ f(f^{-1}(x)) = f\left(\frac{21}{x}\right) = \frac{21}{\left(\frac{21}{x}\right)} = x. \] For \( f^{-1}(f(x)) \): \[ f^{-1}(f(x)) = f^{-1}\left(\frac{21}{x}\right) = \frac{21}{\left(\frac{21}{x}\right)} = x. \] Both checks confirm that the inverse function is correct, so: \( f^{-1}(x) = \frac{21}{x} \) for \( x \neq 0 \). Now, let's dive into some engaging details! The concept of inverse functions has been around for centuries, and mathematicians like René Descartes and Gottfried Wilhelm Leibniz explored relationships between functions and their inverses, making this not just a mathematical exercise but a historical journey through the ages of mathematical evolution. A real-world application of inverse functions can be found in economics, particularly in the realm of supply and demand analysis. For example, if a company has a demand function related to price, knowing the inverse can help determine what price should be set to achieve a desired quantity sold. It’s like having a secret recipe to predict how much customers are willing to pay based on what they want!

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy